Extragenital testing for gonorrhea and chlamydia in health department clinics in Virginia, 2018–2023. - River Pugsley; Nicole Barron; Oana Vasiliu; Sulola Adekoya (Sexually Transmitted Diseases, 2026)
Background: Extragenital testing for chlamydia and gonorrhea infections is now routine in many settings. We assessed temporal and demographic trends in extragenital testing and positivity in public health department clinics in Virginia. Methods: We analyzed urogenital and extragenital chlamydia/gonorrhea laboratory results for clients aged 15 years or older who attended 116 health department clinics from 2018 to 2023. Test volume and positivity was stratified by anatomic site, year, sex, and age. Results: There were 181,471 client visits with valid test results. The proportion of visits with any extragenital testing increased from 19% to 46% during this time. Male clients were twice as likely as females to receive pharyngeal testing (46% vs. 22%) and five times as likely to be tested rectally (15% vs. 3%). Rectal specimen positivity surpassed urogenital positivity for chlamydia (females and males) and gonorrhea (males only). Overall, one-quarter of clients diagnosed with gonorrhea infections were identified exclusively through extragenital testing, as were 9% of clients with positive chlamydia tests. These proportions increased over time and were greater for younger clients and for males relative to females. Two-thirds of extragenital infections would have been missed by urogenital testing alone, including 40% and 49% of females and 86% and 73% of males with extragenital chlamydia and gonorrhea infections respectively. Conclusions: The proportion of clients who received extragenital chlamydia/gonorrhea testing increased over time, extragenital test positivity was high, and it identified infections that would have been missed otherwise. The impact on sexually transmitted infection sequelae and transmission remains unclear.